A legal study on regulating the sale of cigarettes by retailer on children with reference to the control of Tobacco Product Regulations 2004 / Nurfarahana Bahaman - Bahaman, Nurfarahana (2017)
Enforcing laws banning tobacco sales to minors is widely advocated as a way to reduce young people’s access to tobacco and tobacco use. Numerous researches have been done regarding social determinant factors of smoking among adolescents and yet lack of research have been done on impact of retail tobacco access on smoking adolescents in Malaysia. This study aims to set up a specific mechanism to better regulate the sale of cigarettes by the retailers on children with reference to the Control of Tobacco Product Regulations 2004. This is a qualitative study where two sources of data are collected. A face-to-face interview is held with a qualified representative from the Ministry of Health to probe in-depth into the procedures in place as well as enforcement of the law in Malaysia. Findings from this study is that the current legislation which is regulated under the Food Act 1983, is not adequate in enforcing provisions related to tobacco use especially on minors. A new independent act needs to be enacted to regulate the tobacco control on its own as a whole and retail tobacco permitting should be implemented to retailers in order to strictly reduce adolescents’ access to tobacco and tobacco product specifically cigarettes.